Confronting failed government and the Islamic State in Libya. Issue 1 (2nd January 2016) - Unknown
Abstract : The Islamic State has taken advantage of the chaos of 20 months of war in Libya to build a series of bases in the country, expanding its territory and now threatening the country's oil ports. The United States and its allies now face hard decisions about how to confront the militant group.